Pengaruh Kepemimpinan, Tanggung Jawab, Kedisiplinan Dan Kerjasama Terhadap Kinerja Pegawai di Universitas Gorontalo - Nurdin Yusuf (Universitas Gorontalo, 2018)
The study aims to determine and analyze the influence factors of leadership, responsibility, discipline and cooperation affect the performance of employees at Gorontalo University. And To know and analyze the dominant factor that affects the performance of employees at Gorontalo University in Gorontalo.This research was carried out research was conducted at the University of Gorontalo, with consideration of location is one of the central services in the field of education so that employees are required to provide excellent service in a professional manner. Purposive sampling was conducted as many as 105 employees. Data were analyzed using multiple regression analysis. The results showed that Simultaneously shows that the leadership (X1), responsibility (X2), discipline (X3) and cooperation (X4) effect on employee performance (Y). The value R square = 0.827. While the correlation coefficient R = 0.909 Partially indicates that the variable has a positive leadership and dominant to employee performance, Partially indicates that the variable has a positive leadership and dominant to employee performance indicates that the variable Partially responsibility has a positive and significant impact on employee performance partially indicates that the variable has a positive discipline and significant impact on employee performance Partially indicates that the variable has a positive cooperation and significant impact on employee performance, Gorontalo University in Gorontalo.